The Johns Hopkins manual of gynecology and obstetrics - Chou, Betty; Bienstock, Jessica L.; Satin, Andrew J. (Lippincott manual., 2021)
Portable and easy to consult, The Johns Hopkins Manual® of Gynecology and Obstetrics is a trusted on-the-spot reference for virtually any issue you'll encounter in obstetrics, high-risk obstetrics, gynecology, reproductive endocrinology, infertility, and gynecologic oncology. The updated 6th Edition has been reorganized for quick reference, and contains thoroughly revised information culled from the collective expertise of residents and attending physicians at The Johns Hopkins University. -- Provided by publisher.